Diversity behind the mask: ethnicity, gender, and past career experience in a nurse anesthesiology program. - Gibbs DM; Waugaman WR (Journal of Multicultural Nursing & Health (JMCNH))
OBJECTIVES: The purpose of this paper is to describe the student body of a culturally diverse nurse anesthesia program and to identify implications for professional socialization as well as nurse anesthesiology education and practice. METHODS: A five year study (1997-2002) of Barry University's Master of Science Program in Anesthesiology was conducted. Findings were compared with available statistics published by the American Association of Nurse Anesthetists as well as a large national sample in a study by Waugaman and Lu (1999). RESULTS: Findings revealed a diverse student body with respect to ethnicity, gender, and past career experiences. Despite students' varied backgrounds, the median grade point average for the program graduates was 3.8 on a 4.0 scale. Retention rate for the program has averaged about 90% per year. The program also attained a 100% board certification passage rate in 2003. CONCLUSIONS: Diverse students need to be recruited and retained in nurse anesthesiology to be able to deliver culturally sensitive care to multicultural, underserved, and various other populations.